Stock Valuation Analysis using the Dividend Discounted Model Method in Meta Platforms, Inc. Companies - Ega; Rusmawati; Aryanti; Husnaini; Rafiqa Assaf (Formosa Journal of Applied Sciences, 2023)
This study aims to find the intrinsic value of the stock price of the Meta Platforms company. The data collection method uses documentation. The researcher's analytical method is quantitative analysis by calculating the intrinsic value of the stock. The average intrinsic value of the shares exceeds the market price of the shares in the company Meta Platforms, Inc. 2021, namely the intrinsic value of the shares is 384.83 while the market value is 329.22. Under these conditions, the shares of the Meta Platforms, Inc. 2021 Company are in an undervalued condition. From the results of the comparison of intrinsic value with stock market prices above, it can be concluded that the company Meta Platforms, Inc. in 2021 is in an undervalued situation which means it is cheap, so potential investors are advised to buy it while investors should hold it in the hope of a high stock price in the future.